Improved Langevin approach to spinodal decomposition in the chiral transition - Fraga, E. S.; Krein, G.; Ramos, R. O.; Reis, A.; Gobel, C.; DeSaBorges, J.; Magnin, J. (Amer Inst Physics, 2006)
We use an improved Langevin description that incorporates both additive and multiplicative noise terms to study the dynamics of phase ordering. We perform real-time lattice simulations to investigate the role played by different contributions to the dissipation and noise. Lattice-size independence is assured by the use of appropriate lattice counterterms.
Keywords: QCD phase transition; heavy-ion collisions; dissipation in field theory